Risk for alcoholic liver cirrhosis after an initial hospital contact with alcohol problems: A nationwide prospective cohort study. Issue 3 (6th January 2017) - Askgaard, Gro; Leon, David A.; Kjær, Mette S.; Deleuran, Thomas; Gerds, Thomas A.; Tolstrup, Janne S.
Abstract : Alcoholic liver cirrhosis is usually preceded by many years of heavy drinking, in which cessation in drinking could prevent the disease. Alcohol problems are not consistently managed in hospital patients. We followed all Danish patients with an initial hospital contact with alcohol problems (intoxication, harmful use, or dependence) during 1998‐2002 for alcoholic liver cirrhosis development (n = 36, 044). In this registry‐based cohort, we identified predictors of the absolute risk for alcoholic liver cirrhosis. Incidence rate ratios (IRRs) were estimated as the incidence rate of alcoholic liver cirrhosis in these patients relative to the general population. Age and alcohol diagnosis were significant predictors of alcoholic liver cirrhosis risk in men and women, whereas civil status, education, and type of hospital care were not. In men, the 15‐year absolute risk was 0.7% (95% confidence interval [CI], 0.4, 0.8) for 20‐29 years, 5.5% (95% CI, 4.9, 6.2) for 30‐39 years, 9.8% (95% CI, 9.0, 11) for 40‐49 years, 8.9% (95% CI, 8.1, 9.8) for 50‐59 years, 6.2% (95% CI, 5.1, 7.2) for 60‐69 years, and 2.5% (95% CI, 1.7, 3.3) for 70‐84 years. According to alcohol diagnosis in men, the 15‐year absolute risk was 2.6% (95% CI, 2.3, 2.9) for intoxication, 7.7% (95% CI, 6.4, 7.9) for harmful use, and 8.8% (95% CI, 8.2, 9.4) for dependence. The IRR for alcoholic liver cirrhosis in the cohort relative to the general population was 11 (95% CI, 10, 12) in men and 18 (95% CI, 15, 21) in women. Conclusion : Hospital patients with alcohol problems had a much greater risk for alcoholic liver cirrhosis compared to the general population. The risk was particularly increased for patients 40‐59 years and for patients diagnosed with harmful use or dependence. (Hepatology 2017;65:929‐937).